SEA RANCHING OF Holothuria atra: STOCKING DENSITY AND TIME - Retno Hartati; Ambariyanto Ambariyanto; Muhammad Zainuri; Widianingsih Widianingsih (BIOTROPIA, 2021)
Strong market demand, uncontrolled exploitation, and inadequate fisheries resource management have caused the overexploitation of sea cucumbers. Hence, sea ranching has been suggested as an intervention to overcome, or at least minimize, this problem. Since stocking density is one of the most important considerations in sea cucumber rearing, this study aimed to determine the optimal stocking density for the ranching of Holothuria atra. Individuals of H. atra were collected from Panjang Island, Jepara waters, and reared in bottom cages in Teluk Awur waters, Jepara, at densities of 30, 20, or 10 individuals per cage measuring 2 × 2 × 1.8 m (with a bottom area of 4 m²). Stocking of H. atra was conducted three times: at the time of cage installation, during the second month, and during the third month after installation. Characteristics of the bottom sediment (i.e., chlorophyll a, chlorophyll b, phaeophytin, and total carotene) in the sea cucumber habitat, as well as water quality parameters within the cages, were measured monthly. The results showed that the growth of H. atra fluctuated throughout the rearing period. Low stocking density resulted in higher individual weight gain compared to high stocking density. The highest weight gain was observed at a stocking density of 10 individuals per cage during the second stocking month. The highest survival rate (93%) was recorded at a stocking density of 30 individuals per cage during the third stocking month, considering that the sea cucumbers were reared for only three months. The highest mortality occurred at a stocking density of 20 individuals per cage. A low survival rate of 45% was observed during the first stocking period, or after the fifth month of rearing. Fission was observed among H. atra reared in the cages, resulting in smaller individuals. Among the measured parameters, sediment chlorophyll a, chlorophyll b, phaeophytin, and carotene concentrations fluctuated with rearing duration due to feeding activity and bioturbation by sea cucumbers. Overall, the results of this study suggest that a low stocking density of H. atra during the second stocking month promotes higher growth rates.